Oferta da disciplina Libras no ensino fundamental na rede municipal de Castanhal-PA - Silva, Carlos Dyego Batista da (Universidade Federal de São Carlos, 2024)
The teaching of Libras to the entire school community is defended by those interested in the social inclusion of the deaf community, arguing that the more people who use Libras, the greater the social inclusion of deaf people. Based on this thought, the general objective of this research is to reflect on the perceptions of the provision of the Libras subject in the municipal network of a city in Pará, which has been offering the Libras subject as a curricular component for 17 years. This research with a qualitative approach, of an exploratory nature, is also configured as field research. As a data collection instrument, interviews were carried out using semi-structured scripts with the following participants: managers, teachers, students, graduates of the discipline and members of the deaf community. The results point to the creation of possibilities for communicative exchanges between deaf and hearing people through contact with sign language. This linguistic interaction not only breaks down barriers, but also builds bridges of understanding between deaf and hearing subjects. It also promotes knowledge about the existence of sign language, however the teaching of the language is not taking into account the needs of deaf students, and despite the discipline having been in force for 17 years, the social impact is timid.

La enseñanza de Libras a toda la comunidad escolar es defendida por aquellos interesados ​​en la inclusión social de la comunidad sorda, argumentando que cuanta más gente utilice Libras, mayor será la inclusión social de las personas sordas. A partir de este pensamiento, el objetivo general de esta investigación es reflexionar sobre las percepciones sobre la oferta de la asignatura Libras en la red municipal de una ciudad de Pará, que ofrece la asignatura Libras como componente curricular desde hace 17 años. Esta investigación con enfoque cualitativo, de carácter exploratorio, se configura también como investigación de campo. Como instrumento de recolección de datos se realizaron entrevistas mediante guiones semiestructurados a los siguientes participantes: directivos, docentes, estudiantes, egresados ​​de la disciplina y miembros de la comunidad sorda. Los resultados apuntan a la creación de posibilidades para intercambios comunicativos entre personas sordas y oyentes a través del contacto con la lengua de signos. Esta interacción lingüística no sólo derriba barreras, sino que también tiende puentes de comprensión entre personas sordas y oyentes. También promueve el conocimiento sobre la existencia de la lengua de señas, sin embargo la enseñanza de la lengua no está tomando en cuenta las necesidades de los estudiantes sordos, y a pesar de que la disciplina tiene 17 años de vigencia, el impacto social es tímido.
Offer of the Libras subject in elementary school in the municipal network of Castanhal-PA
Oferta de la asignatura Libras en la escuela primaria de la red municipal de Castanhal-PA
Keywords: Língua Brasileira de Sinais; Ensino de Libras; Inclusão escolar; Educação especial; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM